2020
DOI: 10.1097/mpa.0000000000001501
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Nrf2 Protects Against Lipopolysaccharide and Cerulein-Induced Pancreatitis In Vitro and In Vivo

Abstract: Objectives In this study, we focused on the function of nuclear factor E2–related factor 2 (Nrf2) in acute pancreatitis (AP), which has been shown to have protective effects in gliomas, hepatocytes, and astrocytes. Methods Acute pancreatitis cell line and animal model were induced by administration of lipopolysaccharide and cerulein into the cell supernatant or intraperitoneal injection. Oxidative stress status was evaluated by measuring the level of am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Cerulein + lipopolysaccharide (LPS) are often used to induced acute pancreatitis in rodents and in cultured pancreatic acinar cells (Fu et al, 2020;Xiao et al, 2020). Our previous study found that treatment of AR42J cells with cerulein + LPS induced an obvious stress response in the ER (Ren et al, 2019a).…”
Section: Mfg-e8 Alleviates Er Stress In Pancreatic Exocrine Acinar Cellsmentioning
confidence: 99%
“…Cerulein + lipopolysaccharide (LPS) are often used to induced acute pancreatitis in rodents and in cultured pancreatic acinar cells (Fu et al, 2020;Xiao et al, 2020). Our previous study found that treatment of AR42J cells with cerulein + LPS induced an obvious stress response in the ER (Ren et al, 2019a).…”
Section: Mfg-e8 Alleviates Er Stress In Pancreatic Exocrine Acinar Cellsmentioning
confidence: 99%
“…AP being an oxidative stress condition, the Nrf2/Keap1 signaling pathway is activated in the pancreas, but this not sufficient to prevent the disease [ 12 ]. Several studies have shown that the hyper-stimulation of Nrf2 via plant-derived natural compounds such as visnagin or hydroxytyrosol could be a promising strategy against the excessive oxidative stress that characterizes AP [ 41 , 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ]. Recent findings indicate that the nuclear factor E2-related factor 2 (Nrf2) and nucleotide-binding domain leucine-rich repeat containing family, pyrin domain-containing 3 (NLRP3) inflammasome pathways are strongly activated during the development of AP [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, AP cell models were successfully established by the treatment of LPS and CRE, and we observed that LPS and CRE reduced cell viability and facilitate inflammation and pyroptosis in acinar cells. Preceding studies have confirmed the effectiveness of the combination of LPS and CRE in AP models to induce oxidative stress, inflammation, and pyroptosis (5,41,42), further supporting the increase in pyroptosis in AP cell models.…”
Section: Discussionmentioning
confidence: 81%